Development of Obstacle Detection Shoes for Visually Impaired People - Yang, Chang-Min; Jung, Ji-Yong; Kim, Jung-Ja (Sensors and materials, 2020)
For visually impaired people, walking is very important in daily life because it provides independence and mobility. Visually impaired people typically use a white cane to assist them when walking, but it is difficult to detect low obstacles using a white cane. Therefore, many walking assistive devices for obstacle detection have been developed for visually impaired people. However, the gait characteristics of users have not been considered enough. Shoe-type walking assistive devices have the advantage of detecting low obstacles and providing gait balance; however, no such devices have been developed yet. In this study, we developed obstacle detection shoes for visually impaired people, which can detect obstacles based on the foot angle. These obstacle detection shoes included infrared sensors, six-axis sensors, buzzers, and battery packs. The infrared sensors and six-axis sensors were attached to the upper part of the shoes to detect the distance of obstacles and the direction of the shoes. Additionally, the buzzers were placed on nearby ears to provide an alarm. All subjects were asked to walk along a corridor under two conditions: walking with a white cane and walking with the obstacle detection shoes. To evaluate the effectiveness of the developed device, the required time to pass, number of collisions, plantar pressure distribution, and lower limb muscle activity were analyzed during walking. We found that the required time to pass increased, while the number of collisions, peak pressure, and muscle activity decreased significantly when walking with the obstacle detection shoes. Consequently, we suggest that this device could be helpful in providing safety and supporting the stable walking of visually impaired people.